Synthesis and properties of S-alkyl 4-(4-chlorophenyl)-5-(pyrrole-2-yl)-1,2,4-triazole-3-thiol derivatives - Gotsulya, A. S.; Fedotov, S. O.; Zinych, O. L.; Trofimova, T.; Brytanova, T. S.; Гоцуля, Андрій Сергійович; Федотов, Сергій Олегович; Зінич, Олена Леонідівна; Британова, Тетяна Сергіївна (My University, 2023)
Objective: The aim of the work was to develop effective methods for the synthesis of promising heterocyclic systems based on pyrrole and 1,2,4-triazole. In the process of realizing of this aim, 10 new S-alkyl 4-(4-chlorophenyl)-5-(pyrrole-2-yl)-1,2,4-triazole-3-thiol derivatives were synthesized. Material and Method: Chemical structures of synthesized compounds were characterized with elemental analysis, 1H-NMR, LC-MS techniques. The biological potential of the synthesized substances was estimated by the molecular docking method and ADME analysis. Result and Discussion: An optimum method for the synthesis of S-alkyl 4-(4-chlorophenyl)-5-(pyrrole-2-yl)-1,2,4-triazole-3-thiol has been developed. In molecular modeling studies, the compounds were found to be similar to known drugs in some respects. The interaction of each molecule with the crystal structures of cyclooxygenase-2, lanosterol-14α-demethylase in the active site was considered in silico. Pharmacokinetic parameters for a number of the synthesized compounds have been predicted by ADME analysis.
Keywords: 1,2,4-triazole; ADME analysis; docking; synthesis